2007
DOI: 10.1021/ol7018778
|View full text |Cite
|
Sign up to set email alerts
|

Solid-Phase Synthesis of Symmetrical 5‘,5‘-Dinucleoside Mono-, Di-, Tri-, and Tetraphosphodiesters

Abstract: Four classes of phosphitylating reagents were subjected to reactions with aminomethyl polystyrene resin-bound p-acetoxybenzyl alcohol to yield the corresponding polymer-bound mono-, di-, tri-, and tetraphosphitylating reagents. The solid-phase reagents were reacted with unprotected nucleosides (e.g., thymidine, adenosine, 3'-azido-3'-deoxythymidine, cytidine, or inosine) in the presence of 5-(ethylthio)-1H-tetrazole. Polymer-bound nucleosides underwent oxidation with tert-butyl hydroperoxide, deprotection of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 30 publications
(33 reference statements)
0
22
0
Order By: Relevance
“…Formation of pyrophosphate linkages by various chemical methods is widely-known and well-described in the literature. [26,[54][55][56][57] The synthesis of oligomers, consisting of nucleosides joined by pyrophosphate linkages, was done quiet recently. [58] Amidophosphite method was used for the preparation of such modified DNA-oligomers (Scheme 5).…”
Section: Pyrophosphorylationmentioning
confidence: 99%
“…Formation of pyrophosphate linkages by various chemical methods is widely-known and well-described in the literature. [26,[54][55][56][57] The synthesis of oligomers, consisting of nucleosides joined by pyrophosphate linkages, was done quiet recently. [58] Amidophosphite method was used for the preparation of such modified DNA-oligomers (Scheme 5).…”
Section: Pyrophosphorylationmentioning
confidence: 99%
“…2 of pyrophosphate linkages by various chemical methods is also described in the literature. [46][47][48] However, as combination of these approaches was not fruitful, sophisticated protection strategy and new methods for the formation of pyrophosphoric bond were developed, resulting in new strategies for the chemical synthesis of PAR oligomers. 41,49 The ADP-ribose dimer represents the simplest form of PAR and can be considered as a model compound.…”
Section: Introductionmentioning
confidence: 99%
“…28 Our research on the solid-phase synthesis of organophosphorus and organosulfur compounds revealed that the polymer-bound p -acetoxybenzyl alcohol containing amide linker ( 5 ) was more stable than polymer-bound N -Boc p -acetoxybenzyl alcohol even in basic conditions and was used to generate sulfonamides and other organophosphorus compounds in high yields and without the need for extensive purifications of final products. 29,30 Thus, polymer-bound linker 5 instead of polymer-bound N -Boc p -acetoxybenzyl alcohol was selected for the reaction with β-triphosphitylating reagent 6 to generate a new polymer-bound β-triphosphitylating reagent 7 that was used for preparation of nucleoside β-triphosphates including two novel compounds 3 and 4 (Scheme 1). …”
mentioning
confidence: 99%